2019
DOI: 10.3389/fphar.2019.01447
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Effectiveness of Intravenous Contrast-Enhanced Sonography in Chinese Children—A Single Center and Prospective Study in China

Abstract: Background and Objective: Intravenous contrast-enhanced ultrasound (CEUS), using the second-generation ultrasound contrast agent SonoVue®, has been widely used in adults. In 2016, it was approved for pediatric applications by the American Food and Drug Administration (FDA). However, it has not been approved by the Chinese Food and Drug Administration (CFDA). The objective of the study was to evaluate the safety and effectiveness of CEUS in children prospectively at a single center in China. Methods: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The EFSUMB guidelines and position papers on CEUS have reviewed all available evidence and indicated that CEUS is a safe and effective examination in adults [67][68][69]. The series of Mao et al [66], specifically investigating pediatric patients, reports an adverse reaction rate of 6/312 (1.92 %), compared with a reaction rate of 0.9 % in the current study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The EFSUMB guidelines and position papers on CEUS have reviewed all available evidence and indicated that CEUS is a safe and effective examination in adults [67][68][69]. The series of Mao et al [66], specifically investigating pediatric patients, reports an adverse reaction rate of 6/312 (1.92 %), compared with a reaction rate of 0.9 % in the current study.…”
Section: Discussionmentioning
confidence: 47%
“…The safety of CEUS has been well documented in adult patients [61,62], and there have been some reports of the safety in children, assessing smaller numbers, with a similar safety profile as that seen in adults [53,[63][64][65][66]. The EFSUMB guidelines and position papers on CEUS have reviewed all available evidence and indicated that CEUS is a safe and effective examination in adults [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile of UCA is high with very low incidence of side effects [ 2 , 9 ]. The frequency of adverse events associated with the intravenous use of UCA is lower than the one associated with the use of iodinated contrast material at CT and similar to the one associated with the use of gadolinium-based contrast agents [ 2 , 10 ]. However, the long-term effects related to gadolinium-based contrast material deposition in brain tissue are unknown, particularly in small immature babies.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of 173 children, no adverse events were encountered [13]. In a prospective study of 600 injections in 312 children, only 3 mild reactions occurred [11].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…UCA are safe in adults and children [6][7][8][9][10][11][12][13], although safety of UCA in pregnancy is unknown. At our institution, post-pubertal girls undergo screening for possible pregnancy prior to CEUS, similar to before other imaging.…”
Section: Basic Ceus Principles and Safetymentioning
confidence: 99%